Cape Town at war: the city, lived experiences and loyalties, 1914-1919 - Walton, Sarah-Jane (Department of Historical Studies, 2020)
This thesis explores ways in which the First World War affected Cape Town. It addresses the absence of research on urban histories in South Africa and non-European urban histories of the war. It tells of the history in Cape Town and the history of Cape Town during the war. By drawing on a variety of primary sources – government and city records, organisational archives, print media - it demonstrates some of the infrastructural, economic and social consequences of the war on the city. The thesis is structured in three main parts. The first considers the city on the advent of the war and Capetonians' responses to its declaration. This related to the Anglo-Boer War and the 1910 formation of Union, and Cape Town's particular history of Anglicisation. It also explores how war changed the experience of daily life, imbuing the city with war-related sights, sounds and symbols. The second part of the thesis emphasises that the war was a period of considerable infrastructural and demographic change. The city's work-force, too was affected by the war, whilst a rise in living-expenses, and a wartime spread of socialist ideas, led to intensified strike action. This was notable for increased cross-racial co-operation, as well as the marked presence of semi- and unskilled workers organising en-mass for the first time. The third part of the thesis speaks to subjective depictions of Cape Town. It considers three main discourses about the city – ‘slum city,' ‘sin city' and ‘destination city' - indicating the co-existence of multiple and sometimes contrasting representations of wartime Cape Town. Lastly, the war was a period of heightened identifications with Britain, which cut across race, gender and class lines. Nevertheless wartime patriotism was inconsistently sustained, with certain events fuelling feelings of loyalty towards Empire and animosity towards those deemed as ‘disloyal.' Overall it is concluded that although the war has faded in Cape Town's popular memory, it was important to how many Capetonians identified themselves. Moreover it was a significant catalyst for change, informing debates and subsequent policies about health, segregation and the future of South African cities.